Presentation, management and outcome of 32 patients with pregnancy-associated breast cancer: a matched controlled study - Halaška, Michael J; Pentheroudakis, George; Strnad, Pavel; Stankušová, Hana; Chod, Jiří; Robová, Helena; Petruželka, Luboš; Rob, Lukáš; Pavlidis, Nicholas (The breast journal, 2009)
Pregnancy-associated breast cancer (PABC) is a rare and challenging problem. We sought to describe epidemiology, management and outcome of women in whom breast cancer was diagnosed during pregnancy or within one year after delivery. Thirty-two women with PABC were referred to two European Union oncology centers between 1995 and 2007, 16 during pregnancy and 16 within 1 year after delivery. Data concerning diagnosis, management, delivery and fetal and maternal outcome were recorded. A group of 32 patients (matched controls) presenting with nonpregnancy-associated breast cancer (non-PABC) was matched for age at diagnosis, tumor size and stage to each PABC patient. Differences in outcome between the PABC and non-PABC groups were then assessed. Histological features were similar in both groups, except that estrogen receptor-negative tumors were more common in the PABC group. Three patients received chemotherapy and two others underwent surgery during pregnancy, with no excess toxicity or severe maternal/fetal adverse effects. All children in the PABC group were healthy, except for one exposed to epirubicin in utero and born with rectal atresia. Overall survival was similar in PABC and non-PABC patients (p = 0.449). The subgroup of patients with breast cancer diagnosed within one year after delivery showed a shorter time to relapse than controls or patients with gestational cancer (p = 0.0178). PABC is a special situation, necessitating individualized, multi-disciplinary management. Prognosis is similar for women with nongestational cancer matched for age and stage though poorer outcome postpartum should be further investigated.
Keywords: receptory pro estrogeny; kombinovaná terapie; výsledek terapie; Receptors, Estrogen; poruchy v puerperiu; Řecko; Pregnancy Complications, Neoplastic; Combined Modality Therapy; retrospektivní studie; protinádorové látky; Česká republika; Pregnancy; těhotenství; vedení porodu; receptor erbB-2; nádory prsu; Cesarean Section; Antineoplastic Agents; indukovaný potrat; receptory progesteronu; Treatment Outcome; Czech Republic; Abortion, Induced; Receptor, ErbB-2; lidé; Receptors, Progesterone; Greece; ženské pohlaví; Breast Neoplasms; Humans; Delivery, Obstetric; Radiotherapy; Puerperal Disorders; radioterapie; Retrospective Studies; Female; císařský řez; nádorové komplikace v těhotenství